Use of English Teachers' Pedagogical Capital in the Classroom - Bastola, Ganesh Kumar (Curriculum Development Journal, 2022)
This paper aims at exploring the uses and practices of English as a Foreign Language (EFL) Teachers pedagogical capital in the classroom. It examines how the use and usages of EFL teachers’ pedagogical capital affects the way they deal with their students in the language classroom. The research was grounded within the interpretive research paradigm. The in-depth unstructured interview and observation were the research tools under narrative inquiry design. The data were collected from three different participants and themes were substantiated by Clandinin and Connelly to replicate their voices and experiences. The research finding reveals that teachers’ profound knowledge and skills about their capital are useful to integrate various cultures and content in the classrooms. Pedagogically inbuilt potentials of teachers and their pedagogical capital maximally enhance learners’ learning opportunities and foster students’ potential. However, it contributes to teachers’ education by rationalizing the essence of teachers’ pedagogical knowledge to transform our ELT practice in Nepal.